2017
DOI: 10.1371/journal.pone.0185800
|View full text |Cite
|
Sign up to set email alerts
|

Forest litter crickets prefer higher substrate moisture for oviposition: Evidence from field and lab experiments

Abstract: For insects, choosing a favorable oviposition site is a type of parental care, as far as it increases the fitness of its offspring. Niche theory predicts that crickets should show a bell-shaped oviposition response to substrate moisture. However, lab experiments with mole crickets showed a linear oviposition response to substrate moisture. Studies with the house cricket Acheta domesticus also showed a linear juvenile body growth response to water availability, thus adult ovipositing females should respond posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 81 publications
2
6
0
Order By: Relevance
“…Our laboratory experiments showed that the number of eggs laid by female crickets in soil moistened with either alkaline or regular water was similar, indicating that long term spraying of alkaline water to control biting midge population would not affect egg laying site selection of ground arthropods such as crickets. Congruent with the finding of this present study, results of previous studies showed that compared to pH value, soil moisture was a more critical factor in affecting oviposition site choice of crickets [ 21 , 33 ]. Female crickets would lay small number of eggs when soil moisture was low and would lay no eggs when the soil moisture was too high [ 33 ].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Our laboratory experiments showed that the number of eggs laid by female crickets in soil moistened with either alkaline or regular water was similar, indicating that long term spraying of alkaline water to control biting midge population would not affect egg laying site selection of ground arthropods such as crickets. Congruent with the finding of this present study, results of previous studies showed that compared to pH value, soil moisture was a more critical factor in affecting oviposition site choice of crickets [ 21 , 33 ]. Female crickets would lay small number of eggs when soil moisture was low and would lay no eggs when the soil moisture was too high [ 33 ].…”
Section: Discussionsupporting
confidence: 78%
“…This experiment aimed to study whether pH of substrate surface influenced the oviposition site choice of ground arthropods. Crickets were chosen as the model organisms, and we followed the method of de Farias-Martins et al [ 21 ] to set up the oviposition sites. A single gravid female cricket was placed into each of 20 rectangular transparent boxes (L = 28 cm; H = 21 cm; W = 15 cm).…”
Section: Methodsmentioning
confidence: 99%
“…The spatial rearrangements (21 ka, 6 ka, 0 ka and RCP8.5) indicated that the most stable occurrence areas of Endecous are associated with the Atlantic Forest. This highlights moisture as a threshold condition for these crickets, since they depend on substrate moisture for oviposition (De Farias-Martins et al 2017). Considering that caves frequently present high moisture content and climatic stability (Mejía-Ortíz et al 2021, Moldovan et al 2018, Sánchez-Fernández et al 2018, the frequent observations of the genus associated with climatically stable regions within caves also coincide to what is exposed by the models.…”
Section: The Atlantic Rainforests As a Source And Temporal Refuge Of ...mentioning
confidence: 52%
“…All oviposition behaviors presented by E. chape have been reported in other Gryllidae species (Destephano et al 1982, Evans 1983, Sugawara 1993. Some behaviors, like females combing the substrate, may be interpreted as a search for an oviposition site that offers adequate temperature (Destephano et al 1982) and moisture, as indicated by Boake (1984) with N. maya, and tested by Farias-Martins et al (2017) with Ubiquepuella telytokous Fernandes, 2015 (Phalangopsidae), among other qualities that are important choices for offspring success. Similarly, numerous insertions of the ovipositor into the oviposition site may be a method for preparing the oviposition site or a way to lay more eggs, which both ensure greater reproductive success.…”
Section: Discussionmentioning
confidence: 92%